Analisis Yuridis Mengenai Kekaburan Norma Status Pekerja Lepas dalam Sistem Hukum Ketenagakerjaan Indonesia - I Putu Gede Nesa Saputra Yasa (Pusat Riset dan Inovasi Nasional, 2025)
The development of the digital economy has led to a significant increase in the number of freelance workers in Indonesia. Despite their growing contribution to the economy, their legal status within the national employment system remains normatively ambiguous. This research aims to analyze the normative ambiguity of the status of freelance workers in Indonesian legislation and its juridical implications for their legal protection. The research method used is normative juridical with a statute approach and a conceptual approach. The results indicate that Law No. 13 of 2003 concerning Manpower in conjunction with Law No. 6 of 2023 does not explicitly define or regulate the category of freelance workers. Consequently, their legal relationship is often positioned in a grey area between a